Model‐based meta‐analysis of individual International Prostate Symptom Score trajectories in patients with benign prostatic hyperplasia with moderate or severe symptoms. Issue 8 (14th April 2020) - D'Agate, Salvatore; Wilson, Timothy; Adalig, Burkay; Manyak, Michael; Palacios‐Moreno, Juan Manuel; Chavan, Chandrashekhar; Oelke, Matthias; Roehrborn, Claus; Della Pasqua, Oscar
Abstract : Aims: International Prostate Symptom Score (IPSS) is a marker of lower urinary tract symptoms (LUTS) deterioration or improvement in benign prostate hyperplasia (BPH). Whereas changes in IPSS relative to baseline have been used as endpoints in clinical trials, little attention has been given to the time course of symptoms. The current investigation aimed to develop a drug‐disease model to describe individual IPSS trajectories in moderate and severe BPH patients. Methods: A model‐based meta‐analytical approach was used including data from 10 238 patients enrolled into Phase III and IV studies receiving placebo, tamsulosin, dutasteride or combination therapy over a period of up to 4 years. Model predictive performance was assessed using statistical and graphical criteria. Subsequently, simulations were performed to illustrate the implications of treatment with drugs showing symptomatic and disease‐modifying properties in patients with varying disease progression rates. Results: Improvement and worsening of IPSS could be characterized by a model including a sigmoid function which disentangles drug effects from placebo and varying disease progression rates on IPSS. Mean estimate (95% confidence intervals) for the disease progression rate was 0.319 (0.271–0.411) month −1 . Treatment effect on IPSS (DELTA) was found to be 0.0605, 0.0139 and 0.0310 month −1 for placebo, tamsulosin and combination therapy, respectively. In addition, it appears that individual trajectories can be clustered together into different phenotypes describing the underlying disease progression rate (i.e. slow, moderate and fast progressors). Conclusions: The availability of a drug‐disease model enables the evaluation of interindividual differences in disease progression rate, deterioration of symptoms and treatment effects on LUTS/BPH.